A Case of Recurrent Vasculitic Vitreous Haemorrhage in One Eye and Idiopathic Choroidal Granulomas in The Fellow Eye of A Young Individual - Himanshi Aggarwal; Prateek Nishant; Gitanjli Sood; Achala Ramawat; Ajai Agrawal; Sanjeev Kumar Mittal; Ramanuj Samanta (Delhi Journal of Ophthalmology)
A 26-year-old male presented with sudden diminution of vision in right eye (OD) for 15 days. Best-corrected visual acuity (BCVA) was finger counting 1-metre in OD and 6/6 in left eye (OS). Fundus examination revealed fresh vitreous haemorrhage (VH) in OD. Investigations including complete haemogram, VDRL, Mantoux test and Contrast-Enhanced Computed Tomography chest were normal. A presumptive diagnosis of Eales disease was made. Subsequently he also developed multiple small choroidal granulomas in OS. He was started on oral corticosteroid and treated with multiple episodes of scatter-laser and intravitreal bevacizumab in OD for recurrent VH. He ultimately required pars-plana vitrectomy in OD for persistent VH despite anti-VEGF and laser. Choroidal granulomas in OS disappeared after treatment with oral steroid. He maintained BCVA of 6/6 in both eyes after 6-months and was kept under close follow-up. Multimodal approach and combination modality of treatment may be required for optimal outcome in such cases.